Efektivitas Penerapan Teknik Bibliotherapy Melalui Konseling Individual Untuk Peningkatan Konsep Diri Siswa Kelas VIII A SMPN St. Yoseph Noelbaki Kupang Tahun Pelajaran 2023/2024 - Mariance Yuliana Faikusa; Wens Nagul; Dhiu Margaretha (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The problem in this research is whether the application of bibliotherapy techniques through individual counseling is effective for improving the self-concept of class VIII A students at SMPK St. Yoseph Noelbaki for the 2023/2024 academic year? The aim of this research is to determine the effectiveness of applying bibliotherapy techniques through individual counseling to improve the self-concept of class VIII students at ASMPK St. Yoseph Noelbaki for the 2023/2024 academic year. The method used in this research is quantitative descriptive with pre-experimental design (one-group pretest-posttest design). The research instruments used were a self-concept questionnaire and guidelines for implementing bibliotherapy techniques. The t test formula is used by research when analyzing data. The analysis results show that the t_count value is 88.75, while the t_table value at the 5% significance level is 12.71 (t_count > t_(table)). This shows that the application of bibliotherapy techniques through individual counseling is effective for improving the self-concept of class VIII A students at SMPK St. Yoseph Noelbaki for the 2023/2024 academic year. Based on the results of this research, the researcher provides suggestions to: 1) The principal is expected to better coordinate and support the entire BK program so that it is implemented well in order to help students improve their self-concept. 2) Guidance and Guidance Teachers are expected to continuously provide individual counseling services using bibliotherapy techniques to improve students' self-concept. 3) Students are expected to actively participate in individual counseling using bibliotherapy techniques carried out by guidance and counseling teachers to improve students' self-concept.